2013
DOI: 10.1111/irv.12104
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus epidemic periods in an equatorial city of Brazil

Abstract: BackgroundCharacterization of the human respiratory syncytial virus (HRSV) season at the local level has important implications for appropriate decisions on the time period for administration of specific prophylaxis.Objectives(1) To describe five consecutive epidemic periods of HRSV in an equatorial city of Brazil and (2) to show preliminary data on genomic diversity of circulating HRSV.Patients/MethodsNasopharyngeal aspirates of 2885 children attending the emergency room and wards of a public hospital were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…The main climate change during the year in Fortaleza is the rainy season. Previous studies have demonstrated an association between the rainy season and epidemic periods of RSV and influenza, but this did not occur with HAdVs in our study [32,33]. In addition, the correlation between the occurrence of the PIV-3 and the dry season, reported in other studies [32,34], was not observed with HAdVs, even though the detection rates of these viruses were highest in the dry months of September and October.…”
Section: Discussioncontrasting
confidence: 94%
“…The main climate change during the year in Fortaleza is the rainy season. Previous studies have demonstrated an association between the rainy season and epidemic periods of RSV and influenza, but this did not occur with HAdVs in our study [32,33]. In addition, the correlation between the occurrence of the PIV-3 and the dry season, reported in other studies [32,34], was not observed with HAdVs, even though the detection rates of these viruses were highest in the dry months of September and October.…”
Section: Discussioncontrasting
confidence: 94%
“…Our findings relate to other studies that have reported dominance of GA2 and NA1 genotypes coinciding with our study seasons: studies conducted in Belgium (2006–2011), 35 Madrid (2007–2014), Panama (2010–2012), 5 and another in Kenya covering thirteen seasons from 2000 to 2012 9 . A study conducted in Brazil showed replacement of GA5 genotype with GA2 genotype during 2005–2008 seasons 36 . This is an interesting shift in contrast to pre‐millennium reports in which the HRSVA genotypes were shown to co‐circulate with variation in genotype dominance and especially from mid 1970s–2000s 4,5 .…”
Section: Discussionsupporting
confidence: 90%
“… 9 A study conducted in Brazil showed replacement of GA5 genotype with GA2 genotype during 2005–2008 seasons. 36 This is an interesting shift in contrast to pre‐millennium reports in which the HRSVA genotypes were shown to co‐circulate with variation in genotype dominance and especially from mid 1970s–2000s. 4 , 5 The millennium studies have reported a shift from multiple genotype circulation to replacement of an existing genotype and its increased dominance.…”
Section: Discussionmentioning
confidence: 87%
“…[7][8][9][10][11][12][13][14][15][16] Some studies conducted in Brazil have suggested a clear seasonal pattern for RSV infections, with predominance from March to July, and a smaller number of cases in the summer months, especially November to February. [14][15][16][17][18][19] Other viruses have been investigated to a lesser extent, but a seasonal pattern was found for different respiratory viruses in Southern and Southeastern Brazil, where the winter is cold and dry. 10,13,20 Only a few studies were conducted to investigate the prevalence and seasonal patterns of different viral infections among children with an episode of LRTI seen at hospitals from Northeastern Brazil, where the winter is warm and wet.…”
Section: Introductionmentioning
confidence: 99%